Online feedback system for athletes and coaches - Ohtonen, O.; Ruotsalainen, K.; Mikkonen, P.; Heikkinen, T.; Hakkarainen, A.; Leppävuori, A.; Linnamo, V. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Athlete can be measured, analyzed and tracked with several systems. While heart rate has been the most commonly used technology in sports for several decades, more recently different technologies have been introduced in numerous sports. For example, in skiing mobile phone accelerometers have been used for technique detection (Stöggl et al. 2014). The modern mobile technologies have also come into everyday coaching in almost all sports. Mobile apps such as Ubersense and Coaches Eye make it possible to film and analyze sport trials with hand-held devices. However, combining other signals e.g. forces still requires quite a lot of work and time, and the feedback is rarely readily available online. The aim of the Coachtech project was to develop a universal, not sport-specific, real-time and easy-to-use analyzing system for sports that is capable of acquiring and combining analog signals with videos.